Lateral Entry To Teacher Education: Impact on Labor Quantity, Quality and Student Equity - Bettye MacPhail-Wilcox; Lynn K. Bradshaw (Educational Considerations, 1993)
At one extreme are those who contend that the successful completion of a teacher preparation program is an indicator of quality.